Survey and identification of Lobsters in Pointpedro coastal water, Jaffna, Northern Province, Sri Lanka - Kirillawala, K.A.L.K.J.; Sivakumar, P. (University of Jaffna, 2020)
Lobsters are one of the economically important marine crustacean groups occupying variety of habitats. They have a great demand in the domestic market as a delicacy and is a foreign exchange earner for the country. In Sri Lanka, six spiny lobsters have been recorded under two major lobster families. However, taxonomic status of available lobster species is poorly understood in Jaffna peninsula. Therefore, the present study was conducted with the aim of documenting lobsters in Point Pedro coastal waters, Jaffna. A field survey was conducted by suitable field collections of lobsters in Point Pedro coastal waters from September 2019 to February 2020. Samples were initially identified with the help of morphological features at the sample collection site by using the standard keys. At present study, five species of Family Palinuridae were recorded. They are Panulirus versicolor (Lareille, 1804), P. ornatus (Fabricius 1798), P. homarus (Linnaeus, 1758), P. polyphagus (Herbst, 1793) and P. longipes (A. Milne Edwards, 1868). Although this study was the first study on the survey of lobsters in Point Pedro coastal waters, Jaffna, Northern province, Sri Lanka, further field surveys and studies are required to confirm the distribution and occurrence of these lobsters.
Keywords: Coastal waters; Lobsters; Point Pedro